ZnO:Al wide zone “windows” deposited by magnetron sputtering on unheated substrate - Boyko, B.Т.; Khrypunov, G.S.; Yurchenko, G.V. (Вопросы атомной науки и техники, 2000)
Electrical and optical properties of ZnO:Al films deposited on unheated glass substrate by non-reactive RF magnetron sputtering of target ZnO:Al₂O₃ (98/2 wt.%) were studied. It was shown that Zno:Al films with the thickness of 0.75 µm deposited at the magnetron power 130 W and 4 µbar argon pressure with adding of 4·10⁻³ µbar oxygen pressure during the first minute of condensation has the following electrical and optical characteristics: surface, resistance 6 Ω/ and transmittance in visible spectral range about 88%. The ZnO:Al films with such optical and electrical parameters are suitable for substrate configuration highly efficiency thin film solar cells on CuInSe₂ base.